Revealed and Unrevealed Womanly Spiritual Experience in Ta’ziyeh as an Iranian Ritual Performance - Siahpoosh, Maryamalsadat (Feminist theology, 2026)
Ta’ziyeh can be considered the most popular ritual performance in Iranian history after Islam, which is a kind of religious tragedy based on the Islamic-Shia tradition, especially the Battle of Karbala. In addition, since the concepts expressed in Ta’ziyeh contain elements of Liberation theology, Iranian Shiites have used Ta’ziyeh both for mourning and as an allegorical tool to express the message of anti-oppression. Meanwhile, the position of women in both textual and non-textual aspects is challenging. In terms of the text, women appear both as existential heroes and as oppressors, and this duality has played a significant role in the collective consciousness of the Iranian people. However, the feminine non-textual aspect is complicated: on the one hand, in the performance of Ta’ziyeh, mostly men with female clothes have played the role of women, while, on the other hand, the audience and the actor of Ta’ziyeh are in a dynamic relationship that gives a dialectical quality to this performance. Since participation in Ta’ziyeh either as an actor or as an audience contains devotional and spiritual concept and since Ta’ziyeh is a kind of exchange of religious messages and feelings between the actor and the audience in renewing the religious covenant, the issue of gender can be viewed from either point of view. Therefore, this research aims to represent the complexity of women’s position, both textually and non-textually, in the tradition of Ta’ziyeh in Iran.